Health-caring agent for enhancing digestive functions of livestock and poultry - ZHOU YAN; WANG ZONGXIA; HUANG GANGYE (2017)
The invention discloses a health-caring agent for enhancing digestive functions of livestock and poultry. The health-caring agent for enhancing the digestive functions of the livestock and the poultry is prepared from the following raw materials in percentage by weight: 15% of dried orange peel powder, 12% of mangnolia officinalis powder, 6% of fresh ginger powder, 12% of folium cortex eucommiae powder, 8% of radix astragali, and 47% of Chinese date powder. In order to improve the digestive functions of the livestock and the poultry by using the health-caring agent, long-time experiments and summary have been done so as to find a way to fully utilize the Chinese herbal medicine health-caring agent to strengthen the stomach and regulate the physiological functions of the livestock and the poultry; thus, the level of digestion of the livestock and the poultry is improved, the immunity of the livestock and the poultry is enhanced, the disease occurrence rate is reduced by 5-8%, and the breeding benefit is thereb